Pengaruh kualitas pelayanan dan kompetensi karyawan terhadap kepuasan nasabah pada Bank XY Syari’ah cabang Jakarta Pusat - tamba, rousdy safari (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
There are three objectives of this research, namely first, to determine the magnitude of the influence of service quality on customer satisfaction at Bank XY Syari'ah, Central Jakarta Branch. Second, to determine the influence of employee competence on customer satisfaction at Bank XY Syari'ah, Central Jakarta Branch. Third, to determine the magnitude of the influence of service quality and employee competence together on customer satisfaction at Bank XY Syari'ah, Central Jakarta Branch. This is based on the problem of whether customer satisfaction at Bank XY Syari'ah, Central Jakarta Branch is related to service quality and employee competence at the Bank. The conclusion of this research is that service quality has a positive and significant effect on customer satisfaction, employee competence has a positive and significant effect on customer satisfaction, and service quality and employee competence together have a positive and significant effect on customer satisfaction.